2019
DOI: 10.1556/2006.8.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

The role of family and personality traits in Internet gaming disorder: A mediation model combining cognitive and attachment perspectives

Abstract: Background and aims: Gaming disorder was recently recognized as a mental health disorder by the World Health Organization and included in the International Classification of Diseases. Extensive research has been conducted with regard to psychosocial correlates and comorbidity, less so for the developmental mechanisms and the processes leading to the disorder. The association between family factors, personality traits, and gaming has been studied independently but not in combination. To fill this gap in knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 142 publications
(157 reference statements)
6
40
0
14
Order By: Relevance
“…We found that male adolescents were much more likely to have IGD than female adolescents (17.5% versus 7.9%); the observed significant sex difference is consistent with that reported in previous studies (e.g., [4]). In this study, disadvantaged family background (e.g., single-parent family, lower socio-economic status (SES), and lower maternal education level) were found to be significant risk factors of IGD, corroborating previous studies (e.g., [8]). SES is in general negatively associated with both risk behaviors and risk factors of such risk behaviors [8].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We found that male adolescents were much more likely to have IGD than female adolescents (17.5% versus 7.9%); the observed significant sex difference is consistent with that reported in previous studies (e.g., [4]). In this study, disadvantaged family background (e.g., single-parent family, lower socio-economic status (SES), and lower maternal education level) were found to be significant risk factors of IGD, corroborating previous studies (e.g., [8]). SES is in general negatively associated with both risk behaviors and risk factors of such risk behaviors [8].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, disadvantaged family background (e.g., single-parent family, lower socio-economic status (SES), and lower maternal education level) were found to be significant risk factors of IGD, corroborating previous studies (e.g., [8]). SES is in general negatively associated with both risk behaviors and risk factors of such risk behaviors [8]. Attention is hence needed to strengthen prevention of IGD among disadvantaged adolescents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PIU is a disorder that has been listed in DSM-IV and its pathology is almost the same as the Internet gaming disorder or IGD in DSM V. PIU affects the work of cognitive functions in motor control, inhibits the working of brain memory, confiscates concentration and disrupts the part of the brain that is responsible for decision making. But more research is needed because both PIU and IGD still measure addiction dominant in game users, while research shows that non-game internet users also experience the same pathology (Ioannidis et al, 2019;Schimmenti et al, 2019;Throuvala et al, 2019).…”
Section: Problematic Internet Use In Adolescencementioning
confidence: 99%